2016
DOI: 10.1155/2016/5678046
|View full text |Cite
|
Sign up to set email alerts
|

TLR Signalling Pathways Diverge in Their Ability to Induce PGE2

Abstract: PGE2 is a lipid mediator abundantly produced in inflamed tissues that exerts relevant immunoregulatory functions. Dendritic cells (DCs) are key players in the onset and shaping of the inflammatory and immune responses and, as such, are well known PGE2 targets. By contrast, the precise role of human DCs in the production of PGE2 is poorly characterized. Here, we asked whether different ligands of Toll-like receptors (TLRs), a relevant family of pathogen-sensing receptors, could induce PGE2 in human DCs. The onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
1
24
1
Order By: Relevance
“…Using TLR4 triggering as a model for MSK1-driven cDC2 activation, pSS cDC2s produced higher levels of IL-12 and TNF-α, suggesting that the increased expression of MSK1 contributes to their enhanced cytokine production. In addition, MSK1 activation is downstream of several TLRs (31, 40), in-line with the downregulation of miR-130a upon TLR triggering. Thus, pSS cDC2s have decreased expression of miR-130a and increased expression of MSK1, associated with increased production of TNF-α and IL-12.…”
Section: Discussionmentioning
confidence: 65%
“…Using TLR4 triggering as a model for MSK1-driven cDC2 activation, pSS cDC2s produced higher levels of IL-12 and TNF-α, suggesting that the increased expression of MSK1 contributes to their enhanced cytokine production. In addition, MSK1 activation is downstream of several TLRs (31, 40), in-line with the downregulation of miR-130a upon TLR triggering. Thus, pSS cDC2s have decreased expression of miR-130a and increased expression of MSK1, associated with increased production of TNF-α and IL-12.…”
Section: Discussionmentioning
confidence: 65%
“…PGE 2 released by MSCs was identified as the main soluble factor responsible for this inhibition. This conclusion is supported by multiple experimental approaches, including the use of IDM to block PGE 2 production, the pharmacological blocking of the two main PGE 2 receptors expressed by DCs, namely EP2 and EP4, and the increasing of intracellular concentration of cyclic AMP, the main second messenger downstream EP2/EP4 activation ( 53 55 ).…”
Section: Discussionmentioning
confidence: 87%
“…Using PGE 2 , which is synthesized downstream of LPS stimulation and mediates podosome dissolution ( 44 , 46 ), we showed that it maintained DC in an immature state and abolished migration in Matrigel concomitantly to podosome disruption. In contrast to the TLR4 signaling pathway, PGE 2 is not produced upon TLR2 stimulation ( 47 ), and thus podosomes are maintained. Due to the unique ability of DC to dissolve their podosomes, this study further supports the critical role of these cell structures in 3D migration in dense environments.…”
Section: Discussionmentioning
confidence: 99%